Toxicological evaluation of two novel bitter modifying flavour compounds: 3-(1-((3, 5-dimethylisoxazol-4-yl)methyl)-1H-pyrazol-4-yl)-1-(3-hydroxybenzyl)imidazolidine-2, 4-dione and 3-(1-((3, 5-dimethylisoxazol-4-yl)methyl)-1H-pyrazol-4-yl)-1-(3-hydroxybenzyl)-5, 5-dimethylimidazolidine-2, 4-dione. (2016) - Karanewsky, Donald S.; Arthur, Amy J.; Liu, Hanghui; Chi, Bert; Ida, Lily; Markison, Stacy
Abstract: A toxicological evaluation of two novel bitter modifying flavour compounds, 3-(1-((3, 5-dimethylisoxazol-4-yl)methyl)-1 H -pyrazol-4-yl)-1-(3-hydroxybenzyl)imidazolidine-2, 4-dione (S6821, CAS 1119831-25-2) and 3-(1-((3, 5-dimethylisoxazol-4-yl)methyl)-1 H -pyrazol-4-yl)-1-(3-hydroxybenzyl)-5, 5-dimethylimidazolidine-2, 4-dione (S7958, CAS 1217341-48-4), were completed for the purpose of assessing their safety for use in food and beverage applications. S6821 undergoes oxidative metabolism in vitro, and in rat pharmacokinetic studies both S6821 and S7958 are rapidly converted to the corresponding O-sulfate and O-glucuronide conjugates. S6821 was not found to be mutagenic or clastogenic in vitro, and did not induce micronuclei in bone marrow polychromatic erythrocytes in vivo . S7958, a close structural analog of S6821, was also found to be non-mutagenic in vitro . In short term and subchronic oral toxicity studies in rats, the no-observed-adverse-effect-level (NOAEL) for both S7958 and S6821 was 100 mg/kg bw/day (highest dose tested) when administered as a food ad-mix for either 28 or 90 consecutive days, respectively. Furthermore, S6821 demonstrated a lack of maternal toxicity, as well as adverse effects on fetal morphology at the highest dose tested, providing a NOAEL of 1000 mg/kg bw/day for both maternal toxicity and embryo/fetal development when administered orally during gestation to pregnant rats.